The Parkinson-associated human P5B-ATPase ATP13A2 protects against the iron-induced cytotoxicity - Rinaldi, Debora Eugenia (2015)
P-type ion pumps are membrane transporters that have been classified into five subfamilies termed P1-P5. The ion transported by the P5-ATPases is not known. Five genes named ATP13A1-ATP13A5 that belong to the P5-ATPase group are present in humans. Loss of function mutations in the ATP13A2 gene (PARK9, OMIM 610513) underlay a form of Parkinson?s disease (PD) known as Kufor Rakeb Syndrome (KRS), which belongs to the group of syndromes of neurodegeneration with brain iron accumulation (NBIA). Here we report that the cytotoxicity induced by iron exposure was two-fold reduced in CHO cells stably expressing the ATP13A2 recombinant protein (ATP13A2). Moreover, the iron content in ATP13A2 cells was lower than control cells stably expressing an inactive mutant of ATP13A2. ATP13A2 expression caused an enlargement of lysosomes and late endosomes. ATP13A2 cells exhibited a reduced iron-induced lysosome membrane permeabilization (LMP). These results suggest that ATP13A2 overexpression improves the lysosome membrane integrity and protects against the iron-induced cell damage.